How native language and L2 proficiency affect EFL learners' capitalisation abilities: a large-scale corpus study. Issue 2 (August 2019) - Shatz, Itamar
Abstract : Capitalisation is a salient orthographic feature, which plays an important role in linguistic processing during reading, and in writing assessment. Learners' second language (L2) capitalisation skills are influenced by their native language (L1), but earlier studies of L1 influence did not focus on learners' capitalisation, and examined primarily 'narrow' samples. This study examines capitalisation error patterns in a large-scale corpus of over 133, 000 texts, composed by nearly 38, 000 EFL learners, who represent seven different L1s and a wide range of English proficiency levels. The findings show that speakers of all L1s made a large number of capitalisation errors, in terms of errors per word and error proportion (out of all errors), especially at lower L2 proficiency levels. Under-capitalisation was more common than over-capitalisation, though this gap narrowed over time. Interestingly, L1s which share English's Latin script had higher error rates, suggesting that (assumed) perceived similarity between the L1 and the L2 increases interference, though this interference could not be explained only through direct negative transfer. There was also an interaction between L1 influence and L2 proficiency, so that differences between speakers of different L1s became smaller as their L2 proficiency improved.